Artificial intelligence and socioeconomic perspective in Indonesia - Nugroho, Iwan; Hakim, Lukman (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2023)
Artificial Intelligence (AI) has begun to penetrate various social and economic activities in Indonesia. During the pandemic, social distancing activities were able to accelerate the application of AI, and promptly became a safety valve and economic driver in various sector. However, attention to AI implementation opens up space for intensive discourse. AI as a technological element also has social and economic impacts, especially social, economic and political inequality. In the midst of obtaining positive economic benefits, innovation excellence and efficiency, AI in Indonesia still faces problems with agricultural workforce (38.7 million people), ethical and legal aspects, and organizational culture. Solutions from a social and economic perspective anticipating AI include (i) affirmative policies aimed at empowering and increasing the productivity of agricultural workers, (ii) collaboration between IT experts and business practitioners, social science experts and legal practitioners to ensure AI works within a safety and legality framework; and (iii) building an organizational culture in business and public sector management to run a business that meets sustainability principles.JEL ClassificationÂ J00; K20; O38